Aplikasi Ekoenzim Berbasis Kulit Pepaya (Carica papaya L.) Fermentasi Anaerob terhadap Penurunan Kadar FFA Crude Palm Oil - Rafila; Zakwan (Cannarium, 2026)
High free fatty acid (FFA) content in Crude Palm Oil (CPO) is a critical quality issue that directly affects market value and export eligibility. This study aimed to produce eco-enzyme through anaerobic fermentation of papaya peel (Carica papaya L.) waste and to evaluate the effect of eco-enzyme concentration on FFA content and moisture content of CPO. Eco-enzyme was prepared at a papaya peel : molasses : water ratio of 3:1:10 and fermented for approximately 90 days, yielding a product with pH 3.8 and TDS 4,500 ppm. A completely randomized design with three concentration levels 10% (P1), 20% (P2), and 30% (P3) was applied, each replicated three times, at 60°C for 60 minutes. Results showed that eco-enzyme consistently reduced FFA from 52.72% (K0) to 41.17% (P3), with the highest reduction efficiency of 21.90%. Moisture content increased proportionally from 0.57% (K0) to 0.647% (P3). Statistical analysis confirmed significant treatment effects on both parameters (p<0.05). This study demonstrates that papaya peel eco-enzyme exhibits measurable biocatalytic activity on CPO and holds potential as a green technology alternative in palm oil processing. Keywords: eco-enzyme; papaya peel; crude palm oil; free fatty acid; anaerobic fermentation